Immune function in athletes versus nonathletes - Nieman, D. C.; Brendle, D.; Henson, D. A.; Suttles, J.; Cook, V. D.; Warren, B. J.; Butterworth, D. E.; Fagoaga, O. R.; Nehlsen-Cannarella, S. L. (International Journal of Sports Medicine, 1995)
The purpose of this study was to compare natural killer cell cytotoxic activity (NKCA) and Con A-induced lymphocyte proliferation (T cell function) in athletes versus nonathletes, with measurement of natural killer (NK) and T cells to allow a comparison on a "per-cell" adjusted basis. Eighteen young male endurance athletes (10 runners and 8 cyclists) with a mean VO2max of 70.7 +/- 1.3 ml.kg-1.min-1 and 6.6 +/- 0.8 years of competitive experience were compared with 11 nonathletic male adults (47.6 +/- 3.1 ml.kg-1.min-1). Concentrations of circulating leukocyte and lymphocyte subsets, including NK and T cells, were not significantly different between groups. NKCA and T cell function also did not differ between groups, whether expressed unadjusted or adjusted on a per-cell basis. For all subjects combined, both NKCA and T cell function were unrelated to VO2max (r = 0.005, p = 0.98; r = 0.007, p = 0.97, respectively). These data do not support the contention that immune function, as measured in this study, is altered in endurance athletes.